Environmental Geophysical Study of the Groundwater Mineralization in a Plot of the Cotonou Littoral Zone (South Benin) - Yalo Nicaise; Descloitres Marc; Alassane Abdoukarim; Mama Daouda; Boukari Moussa (International Journal of Geophysics)
Geophysical investigations comprising electrical resistivity and electromagnetic conductivities methods were deployed in a 350 m2 sector, strewn with 11 wells. Within the framework of an environmental study on a small scale in the south of Benin, the water conductivity of these wells was measured to determine in a direct way mineralization of the coastal water table in the littoral zone. This environmental study aimed to prospect by the geophysical methods the space extension of the water table mineralization obtained by direct measurements of water conductivity in the well and the depth of the fresh water/salted water interface in the coastal aquifer. Electromagnetic measurements of conductivities made it possible to chart a gradient of mineralization in the northwest direction. The logs of vertical electric soundings showed a deepening of the fresh water/salted water interface in the southern part and its rupture in the northern part. The electrical resistivities of the interface are sensitive to the degree of its mineralization. It has been observed that the geophysical methods in electrical and electromagnetic prospection are a great contribution to the environmental study of the water table mineralization in the littoral zone for a sustainable management of the water resource.